An Assessment of Port Site Infection in Patients Underwent Laparoscopic Cholecystectomy - Javed, Saleem; Sherani, Azizullah Khan; Bhutta, Irtiza Ahmed (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To assess the port site infection in patients underwent laparoscopic cholecystectomy. Material and methods: The descriptive study was conducted at Department of Surgery, Sandeman Provincial Hospital Quetta from February 2021 to August 2021. Total 90 patients of gallstone, both male and female, age between 20-70 years and ASA grade II and III were recruited. All the selected patients were underwent laparoscopic cholecystectomy. All the surgeries were performed under general anesthesia. Port site infection was assessed in selected patients. Results: Mean age of the patients was 41.28 ± 13.75 years. Out of 90 patients of gallstone, port site infections was found in 8 (9%) patients. Two age groups (20-45 years and 46-70 years) were created. Total 55 (61.11%) patients were between 20-45 years while 35 (38.89%) patients were between 46-70 years. Port site infection was found in 4 (7.27%) and 4 (11.43%) patients respectively. Association of port site infection with age group was not significant (P = 0.706). Males were 34 (60.71%) and females were 56 (62.22%). Port site infection was noted in 2 (5.88%) males while in 6 (10.71%) females. Association of port site infection with gender was not significant (P= 0.705). Conclusion: Results of present revealed that port site infection was developed in few patients after laparoscopic cholecystectomy. Most of the patients were between 20-45 years. Females were more victim of gallstone as compared to males. Obese and non-diabetics had not association with development of port site infection.